2019
DOI: 10.13189/ujer.2019.071619
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Integrated and Holistic Education System (Ihes) Program in Gema Nurani Integrated and Holistic Islamic Elementary School, Bekasi, West Java

Abstract: This study aims to evaluate design, installation, process, outcome, benefit and cost in implementation of Integrated and Holistic Educational System (IHES) model in Gema Nurani Integrated and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The limitations of Sholeh & Trihantoyo's research [38] were that it had not shown most dominant aspects of positive and negative inequalities affect the effectiveness of the teachers' duties implementation in their preparation as headmaster. The limitations of Setiawan et al's research [39] were that it had not shown in detail the dominant aspects that need improvement in supporting the implementation of the IHES (Integrated and Holistic Education System) program. The limitations of Aw's research [40] were that it had not shown the dominant aspects that need to be maintained in realizing the effectiveness of public relations programs in encouraging synergistic collaboration between industry and schools.…”
Section: Respondent-40mentioning
confidence: 97%
“…The limitations of Sholeh & Trihantoyo's research [38] were that it had not shown most dominant aspects of positive and negative inequalities affect the effectiveness of the teachers' duties implementation in their preparation as headmaster. The limitations of Setiawan et al's research [39] were that it had not shown in detail the dominant aspects that need improvement in supporting the implementation of the IHES (Integrated and Holistic Education System) program. The limitations of Aw's research [40] were that it had not shown the dominant aspects that need to be maintained in realizing the effectiveness of public relations programs in encouraging synergistic collaboration between industry and schools.…”
Section: Respondent-40mentioning
confidence: 97%
“…Learning innovation in IRE, had to be acknowledged by the academician, that observed in many discourses. From the contemporary issues in Islamic Studies in IRE, such as gender [4], politics, and human rights [5], toward the learning issues, such as the curriculum, the learning evaluation [6], and the learning contents. Especially in Higher Education, IRE has to modify into the creative learning model, in the sense of optimizing the technology and the learning media [7].…”
Section: Introductionmentioning
confidence: 99%